Morris water maze learning in Long-Evans rats is differentially affected by blockade of D1-like and D2-like dopamine receptors - Stuchlik, Ales; Rehakova, Lenka; Telensky, Petr; Vales, Karel (Neuroscience letters, 2007)
Dopaminergic neurotransmission is involved in several brain functions including spatial cognition. In the present study we examine the effects of systemic administration of D1-like receptor antagonist SCH23390 and D2-like receptor antagonist sulpiride on the acquisition of the Morris water maze task. We used visible versus hidden platform versions of the MWM in order to distinguish between the effects of the drugs on the procedural versus cognitive aspects of the task. SCH23390 was found to prolong escape latencies to the visible platform at a higher dose (0.05mg/kg), whilst the lower dose (0.02mg/kg) left both procedural and cognitive functions almost unchanged. SCH23390 was also found to reduce swimming speed. Sulpiride did not affect the visible platform learning at any of three doses studied (30, 60 and 100mg/kg); the highest dose of sulpiride (100mg/kg) impaired place navigation to the hidden platform, without affecting the swim speed. The results of the present study show a difference in the involvement of D1-like and D2-like receptors in the MWM acquisition.
Keywords: antagonisté dopaminu D2; krysa rodu Rattus; Animals; Behavior, Animal; Rats, Inbred LEC; Maze Learning; chování zvířat; mužské pohlaví; zvířata; receptory dopaminu D1; Male; Receptors, Dopamine D1; bludiště - učení; antagonisté dopaminu; Dopamine Antagonists; potkani inbrední LEC; Rats; Dopamine D2 Receptor Antagonists